The Impact of Financial Literacy and Financial Behavior on the Financial Management of Oil Palm Farmers in Sipispis Subdistrict - Eben Ezer Sinaga; Ramadhan Harahap; Noni Ardian (Journal of Management, Economic, and Accounting, 2026)
This study aims to empirically examine the influence of financial literacy and financial behavior on the financial management of oil palm farmers in Sipispis Subdistrict. The background of this study is based on the phenomenon of farmers’ still-low understanding of basic financial concepts and the existence of financial behaviors that are not yet fully rational, such as the habit of mixing business finances with personal finances. The research method employed is a quantitative approach using primary data collected through the distribution of questionnaires to 97 oil palm farmer respondents in Sipispis Subdistrict. The data analysis techniques applied include classical assumption tests, multiple linear regression analysis, and hypothesis testing via the t-test (partial) and F-test (simultaneous) using SPSS software. The results of the study indicate that: (1) Financial literacy has a partial, positive, and significant effect on business financial management, meaning that increased financial knowledge will improve farmers’ ability to manage their businesses. (2) Financial behavior has a partial, positive, and significant effect on business financial management. (3) Simultaneously, financial literacy and financial behavior have a significant effect on the financial management of oil palm farmers in Sipispis Subdistrict, with a contribution (R-Square) of 61.1%. The remaining 38.9% is influenced by other variables outside the scope of this study. These results underscore the importance of enhancing financial literacy and fostering disciplined financial behavior to ensure the sustainability of farming businesses.